Determinants of diarrheal diseases among under five children in Jimma Geneti District, Oromia region, Ethiopia, 2020: a case-control study - Dejene Mosisa; Mecha Aboma; Teka Girma; Abera Shibru (BMC, 2021)
Abstract Background Globally, in 2017, there were nearly 1.7 billion cases of childhood diarrheal diseases, and it is the second most important cause of morbidity and mortality among under-five children in low-income countries, including Ethiopia. Sanitary conditions, poor housing, an unsanitary environment, insufficient safe water supply, cohabitation with domestic animals that may carry human pathogens, and a lack of food storage facilities, in combination with socioeconomic and behavioral factors, are common causes of diarrhea disease and have had a significant impact on diarrhea incidence in the majority of developing countries. Methods A community-based unmatched case-control study was conducted on 407 systematically sampled under-five children of Jimma Geneti District (135 with diarrhea and 272 without diarrhea) from May 01 to 30, 2020. Data was collected using an interview administered questionnaire and observational checklist adapted from the WHO/UNICEF core questionnaire and other related literature. Descriptive, bivariate, and multivariate binary logistic regression analyses were done by using SPSS version 20.0. Result Sociodemographic determinants such as being a child of 12-23 months of age (AOR 3.3, 95% CI 1.68-6.46; P < 0.05) and mothers'/caregivers' history of diarrheal diseases (AOR 7.38, 95% CI 3.12-17.44; P < 0.05) were significantly associated with diarrheal diseases among under-five children. Environmental and behavioral factors such as lack of a hand-washing facility near a latrine (AOR 5.22, 95% CI 3.94-26.49; P < 0.05), a lack of hand-washing practice at critical times (AOR 10.6, 95% CI 3.74-29.81; P < 0.05), improper domestic solid waste disposal (AOR 2.68, 95% CI 1.39-5.18; P < 0.05), and not being vaccinated against rotavirus (AOR 2.45, 95% CI 1.25-4.81; P < 0,05) were found important determinants of diarrheal diseases among under-five children. Conclusion The unavailability of a hand-washing facility nearby latrine, mothers'/caregivers' history of the last 2 weeks' diarrheal diseases, improper latrine utilization, lack of hand-washing practice at critical times, improper solid waste disposal practices, and rotavirus vaccination status were the determinants of diarrheal diseases among under-five children identified in this study. Thus, promoting the provision of continuous and modified health information programs for households on the importance of sanitation, personal hygiene, and vaccination against rotavirus is fundamental to decreasing the burden of diarrheal disease among under-five children.